MACHADO DE ASSIS: INTERSECTIONS AND CONTRASTS BETWEEN THEATRICAL CRITICISM AND THE SHORT STORIES OF THE JORNAL DAS FAMÍLIAS - De Souza Andrade, Anderson [UNESP]; Beline, Heloisa Viccari Jugeick [UNESP] (FapUNIFESP (SciELO), 2023)
The present work aims to present points of íntersection and contrasts between the theatrical critic Machado de Assis and the short story writer. As he believed that the newspaper and the theater were at the service of moral instruction, it ispossible to bring the critic closer andfarther awayfrom the short story writer at a time when he practically carried out both activities:from 1862 to 1864 as a censor, and from 1864 onwards in the Jornal das Familias. For this, the study begins with a comparison oftheprogram letter ofthe Jornal das Familias with the rules established by the Brazilian Dramatic Conservatory and, later, with the sixteen opinions of Machado in the position of censor, in order to observe how the concept and valúes of morality were constructed.
MACHADO DE ASSIS: INTERSECÇÕES E CONTRASTES ENTRE A CRÍTICA TEATRAL E OS CONTOS DO JORNAL DAS FAMILIAS
Keywords: Jornal das Familias; Machado deAssis; theatrical criticism